2004
DOI: 10.18388/abp.2004_3599
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic peptide substrates for carboxydipeptidase activity of cathepsin B.

Abstract: Cathepsin B is a lysosomal cysteine protease exhibiting mainly dipeptidyl carboxypeptidase activity, which decreases dramatically above pH 5.5, when the enzyme starts acting as an endopeptidase. Since the common cathepsin B assays are performed at pH 6 and do not distinguish between these activities, we synthesized a series of peptide substrates specifically designed for the carboxydipeptidase activity of cathepsin B. The amino-acid sequences of the P(5)-P(1) part of these substrates were based on the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Since the activation of this plant enzyme is not trivial, we examined its activity after this process using the FRET Dabcyl-YAKGNGL-Edans substrate. The nonfluorescent peptide turns into the fluorescent GL-Edans (λ ex = 340 nm, λ em = 490 nm) product only when the enzyme is active (Figure A,B) . Because this test is based on substrate hydrolysis, ligase activity has also been examined using model peptides containing recognition termini, YKLANGL and GVGKY-NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the activation of this plant enzyme is not trivial, we examined its activity after this process using the FRET Dabcyl-YAKGNGL-Edans substrate. The nonfluorescent peptide turns into the fluorescent GL-Edans (λ ex = 340 nm, λ em = 490 nm) product only when the enzyme is active (Figure A,B) . Because this test is based on substrate hydrolysis, ligase activity has also been examined using model peptides containing recognition termini, YKLANGL and GVGKY-NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin B, a ubiquitous cysteine protease, is a demonstrated candidate for this application. Cathepsin B is primarily localized in endo/lysosomes, its cleavage substrates have been well-characterized, and it is upregulated in a wide variety of cancers . While cathepsin B can be secreted in a variety of cancer cells, it has previously been employed for the selective intracellular degradation of a polymer conjugate of the angiogenesis inhibitor TNP-470 , and a nucleic acid delivery vehicle .…”
Section: Discussionmentioning
confidence: 99%
“…To address both the stability and conjugation limitations of the disulfide linkage, a synthetic strategy has been employed that creates a selectively cleavable BIM peptide macromonomer (Figure ). The macromonomer contains the BIM peptide sequence capped with the well-characterized cathepsin B substrate Phe-Lys-Phe-Leu (FKFL). This substrate is flanked on either side by a six carbon spacer (6-aminohexanoic acid (Ahx)) to facilitate steric access of the cathepsin enzyme in the context of the surrounding PEG grafts. The peptide is functionalized on its N-terminus with methacrylamide and directly and stably polymerized into a multifunctional diblock copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, they found increases in expression and activity of cathepsin B in invadosomes and they propose that cathepsin B participates in invasion of the colon cancer cells by activating zymogens of MMPs. The pH optima for the two proteolytic activities of cathepsin B are acidic with that for the carboxydipeptidase activity more acidic than that for the endopeptidase activity [53]. The elegant studies by Busco et al [54] show that the peri-invadopodial space of breast cancer cells is acidified by NHE1, a Na+/H+ exchanger isoform, which would be consistent with a local environment that enhances cathepsin B activity.…”
Section: Acidosis and Invadopodiamentioning
confidence: 95%